2023
DOI: 10.1039/d2ra07952f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive properties and on-demand magnetic response of lignin@Fe3O4 nanoparticles at castor oil–water interfaces

Abstract: Lignin@Fe3O4 nanoparticles adsorb at oil–water interfaces, form Pickering emulsions, induce on-demand magnetic responses to break emulsions, and can sequester oil from water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The Fe 3 O 4 nanoparticles were encapsulated with Kraft lignin solubilized in 1 wt% ammonium hydroxide to produce a 3:1 w:w ratio of lignin@Fe 3 O 4 nanoparticles. The detailed procedure to synthesize lignin@Fe 3 O 4 nanoparticles has been reported in our previous publications [33][34][35], and a summary of the procedure can be found in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe 3 O 4 nanoparticles were encapsulated with Kraft lignin solubilized in 1 wt% ammonium hydroxide to produce a 3:1 w:w ratio of lignin@Fe 3 O 4 nanoparticles. The detailed procedure to synthesize lignin@Fe 3 O 4 nanoparticles has been reported in our previous publications [33][34][35], and a summary of the procedure can be found in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…This is because of the dispersant nature of lignin in many industrial and laboratory-scale applications [31,36]. Recently, we demonstrated the adsorptive and magnetic response of lignin:Fe 3 O 4 at a mass ratio of 3:1 [33]. Hence, we used the same ratio for analyzing the thermal conductivity enhancement caused by introducing lignin@Fe 3 O 4 into agar-based suspensions in this study.…”
Section: Morphological Characterization: Transmission Electron Micros...mentioning
confidence: 99%
“…The organic polymer chain segments were combined with inorganic material substrates to prepare composite microspheres with specialized amphiphilic structures, which could be used as environmentally responsive particle emulsifiers. Currently, stimulus-responsive nanoparticle emulsifiers have been reported as pH, thermal, photographic, CO 2 /N 2 , magnetism, thermal/pH, thermal/CO 2 , pH/photographic, etc. Xi et al reported that a layer of pure sodium caseinate (NaCas) coated on the surface of bare SiO 2 particles was used to prepare hybrid nanoparticles with pH-responsive properties as Pickering emulsifiers, and the emulsion steady state changes were investigated under different pH environments .…”
Section: Introductionmentioning
confidence: 99%
“…5 Fortunately, modifying stimulus-responsive groups on NPs enables emulsification and demulsification processes upon stimulation, which effectively addresses the aforementioned issues. 6,7 Currently, several types of stimulus-responsive emulsifiers have been reported, including pH-responsive, [8][9][10] temperature-responsive, [11][12][13] CO 2 -responsive, [14][15][16] light-responsive, 17,18 mechanical-responsive, 19 magnetic-responsive, [20][21][22] REDOX-responsive 23,24 and multi-responsive. Among them, magnetic responsive emulsions have garnered widespread attention due to their advantages of low toxicity, simple operation, fast response speed, high reusability, and excellent controllability.…”
Section: Introductionmentioning
confidence: 99%